A two-component system signaling hub controls enterococcal membrane remodeling in response to daptomycin - Cristina Colomer-Winter; Zeus J. Nair; Jerome Y. J. Chua; Soukayna Jabli; Mélanie Roch; Amaury Cazenave-Gassiot; Roberto Sierra; Diego O. Andrey; Shu-Sin Chng; Kimberly A. Kline (Proceedings of the National Academy of Sciences, 2026)
Daptomycin is a last resort antibiotic used to treat vancomycin-resistant enterococcal infections, but daptomycin resistance (DAP R ) arises quickly during treatment. Resistance is due to sequential acquisition of point mutations in the two-component system LiaFSR and in cardiolipin synthases and is associated with alteration of phospholipid and glycolipid membrane composition. The molecular mechanisms underlying these lipid changes are currently unknown. Similarly, it is unclear why mutations in liaFSR occur prior to mutations in cls . We found that Enterococcus faecalis remodels membrane composition as a phenotypic response to daptomycin that parallels the membrane composition of DAP R strains. The enrichment in glycolipids that follows antibiotic exposure is due to LtaS1, the main lipoteichoic acid (LTA) synthase of E. faecalis . LTA production is primarily governed by LiaFSR and SapRS, which directly couples antibiotic sensing with membrane lipid remodeling. Together, our results provide a unifying mechanism that drives phenotypic membrane fortification in a gram-positive pathogen which simultaneously predisposes the cell to acquire genetic high-level daptomycin resistance.